Marketing violence: the affective economy of violent imageries in the Dutch Republic - Korsten, Frans-Willem (Cambridge elements. Elements in histories of emotions and the senses, 2023)
This volume describes the development of an affective economy of violence in the early modern Dutch Republic through the circulation of images. It outlines that while violence became more controlled in the course of the 17th century, with fewer public executions for instance, the realm of cultural representation was filled with violent imagery: from prints, atlases and paintings, through theatres and public spectacles, to peep boxes. It shows how emotions were evoked, exploited, and controlled in this affective economy of violence based on desires, interests and exploitation.